Multi-technique approach for the assessment of historical masonry constructions - Fernandes, Francisco Manuel Carvalho Pinto (2013)
Publicado em : "Damage Assessment of Structures X", ISBN 978-3-03785-796-0, Serie "Key Engineering Materials", vol. 569 - 570